The Other’s Other: Otherness, Difference and Asymmetry in Adam Smith’s Theory of Moral Sentiments - Campos Salvaterra, Valeria (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The following work aims to analyze the psychological basis and the moral structure of the Theory of Moral Sentiments by Adam Smith, from the notions of otherness, difference and asymmetry. I will attempt to show the key role that asymmetric interaction with another human being has in the configuration of a morality based on impartial judgment, which thus emerges from a gradual alteration of self-consciousness. This implies that moral consciousness is a consciousness determined by the reception of otherness, whose judgment is not characterized by self-reference, but by an external reference: the ultimate reference for a subject to judge relies in the other, or in others, as current and potential spectators of its conduct, and not in himself. From here, we will show how the notion of equality that underpins justice as primary point of morality, is actually a second moment constructed from an asymmetric structure that is ubiquitous in the theory of Smith.
Keywords: morality; impartiality; otherness; difference; asymmetry; heteroreference; justice.